2006
DOI: 10.1016/j.tiv.2006.01.004
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of using comet assay and γH2AX foci formation in the detection of N-methyl-N′-nitro-N-nitrosoguanidine-induced DNA damage

Abstract: Comet assay is a useful technique in the detection of DNA damages, particularly DNA strand breaks; and it has been utilized to show that a potent carcinogen N-methyl-N'-nitro-N-nitrosoguanidine (MNNG), can induce such damages. Recently, gammaH2AX foci formation has been suggested as another sensitive way to detect DNA double strand breaks (DSBs). However, there is no systematic comparison being conducted to evaluate the consistency of these two methods. Using MNNG as a model chemical, the sensitivity of neutra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 22 publications
4
54
0
Order By: Relevance
“…Induction of DNA damage can be determined by the analysis of γH2AX accumulation in the nucleus (Yu et al, 2006). The results from the present study demonstrated that 18α-glycyrrhetinic acid significantly increased the population of HR5-CL11 cells possessing more than four γH2AX foci.…”
Section: Discussionsupporting
confidence: 48%
“…Induction of DNA damage can be determined by the analysis of γH2AX accumulation in the nucleus (Yu et al, 2006). The results from the present study demonstrated that 18α-glycyrrhetinic acid significantly increased the population of HR5-CL11 cells possessing more than four γH2AX foci.…”
Section: Discussionsupporting
confidence: 48%
“…Among the various types of DNA damage, DSBs are the most severe. ␥H2AX (the phosphorylated form of H2AX) focus formation has been gradually accepted as a sensitive indicator of DSBs (38,39). Hence, A549 cells were infected with 10 CFU/cell of M. pneumoniae and then subjected to immunofluorescence microscopy to evaluate the formation of ␥H2AX foci.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we further evaluated the generation of reactive oxygen species (ROS) in M. pneumoniae-infected cells. In addition, as ROS are known to induce DNA damage, we also used ␥H2AX focus formation, a new indicator of DNA double-strand breaks (DSBs) (38,39), to determine whether M. pneumoniae can cause DNA damage through the action of ROS. plasma broth base CM403 (Oxoid, Hampshire, United Kingdom), mycoplasma selective supplement G SR59 (Oxoid), 0.5% glucose, and 0.002% phenol red at 37°C in the presence of 5% CO 2 .…”
mentioning
confidence: 99%
“…Phosphorylation of H2AX is an early event in the ATM-dependent DNA damagesignaling pathway, which has been shown to be active in both myoblasts and myotubes after induction of DSB by ionizing radiation exposure (21). Evidence is accumulating that ␥H2AX foci also identify DNA damage-containing structures other than DSB (22). In the case of myoblasts, ␥H2AX foci were exclusively present in S-phase cells, indicating that they mark the formation of DSB produced by the replication of DNA templates containing SSB.…”
Section: Discussionmentioning
confidence: 99%